Keragaman Konsumsi Pangan dan Kejadian Anemia pada Ibu Hamil di Kabupaten Sumenep Madura - Dyan Fajar Christianti; Faisal Anwar; Cesilia Meti Dwiriani (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Pregnant women in Indonesia whose anemic reach 48,9%. The purpose of this study was to analyze thecorrelation between dietary diversity and anemia in pregnant women in Sumenep District, Madura. This study wasa cross-sectional design. The population of this study was 411 pregnant women in four selected health centers inSumenep District. Subjects were all stage of pregnancy (trimester I, II, III) which numbered 200 pregnant womenwho were selected by proportional random sampling. Data were collected through interviews using a questionnaireand direct measurement. The data used consisted of socio-economic status, history of pregnancy, MUAC, hemoglobinconcentration, and Minimum Dietary Diversity-Women (MDD-W) score. Data analysis used the spearmantest to determine the correlation between MDD-W score and hemoglobin concentration in pregnant women.The result showed that 51,5% of pregnant women were anemic. The MDD-W score for anemia and non-anemiagroups was low (4,8±1,2 vs 4,8±1,6). Spearman test showed that the MDD-W score was not associated with hemoglobinconcentration (p>0,05). Factors of significantly associated with haemoglobin concentration were includinggestational age (r=-0,148; p=0,036), BMI pre-pregnancy (r=0,145; p=0,041), and mid-upper arm circumference(r=0,231; p=0,001). Factors related to anemia in pregnant women were the gestational age, nutritional status inpre-pregnancy, and MUAC, while dietary diversity was not related to the incidence of anemia in pregnant women